Improving the Endosomal Escape of Cell-Penetrating Peptides and Their Cargos: Strategies and Challenges - Jean-Philippe Pellois; Ting-Yi Wang; Ryan Baker; Nandhini Muthukrishnan; Alfredo Erazo-Oliveras (MDPI AG, 2012)
Cell penetrating peptides (CPPs) can deliver cell-impermeable therapeutic cargos into cells. In particular, CPP-cargo conjugates tend to accumulate inside cells by endocytosis. However, they often remain trapped inside endocytic organelles and fail to reach the cytosolic space of cells efficiently. In this review, the evidence for CPP-mediated endosomal escape is discussed. In addition, several strategies that have been utilized to enhance the endosomal escape of CPP-cargos are described. The recent development of branched systems that display multiple copies of a CPP is presented. The use of viral or synthetic peptides that can disrupt the endosomal membrane upon activation by the low pH of endosomes is also discussed. Finally, we survey how CPPs labeled with chromophores can be used in combination with light to stimulate endosomal lysis. The mechanisms and challenges associated with these intracellular delivery methodologies are discussed.